The Long 1960s in Asia - Claudia Derichs; Kamran Asdar Ali (International Quarterly for Asian Studies, 2021)
A number of studies, publications, conferences and anniversary events took place in 2018 to commemorate the 50th birthday of the legendary year 1968. These were accompanied by a raft of scholarly and popular assessments of the “long 1960s”, the “global sixties” and/or the “radical sixties”. The predominant empirical sites for analysis and retrospective were Western Europe and the United States of America. Other world regions were discussed to a clearly lesser extent. Apart from the crucial event of the Vietnam War, the (long) 1960s in Asia did not figure very prominently in the various publications on the topic. This issue of IQAS seeks to focus on the 1960s in Asia, covering East, Southeast and South Asia and discussing the decade from perspectives that have often escaped notice. It sheds a critical light on the notion of the “global sixties” and focuses on the local in order to grasp the spirit of the 1960s in selected Asian countries. It looks at individual nation-states but also transcends their borders, tracing transnational and transregional connectivities, mobilities and relations. It reminds us of radical junctures in countries’ histories that did not pave the way for freedom, peace and democracy – as conventional connotations of “1968” and “the sixties” predominantly suggest. The contributions to this issue thus cover the dark as well as the light side of the 1960s and share the conviction that research on this revolutionary decade’s ramifications in Asia is still a field with many blank spots.